Development of an Enzyme-Linked Immune Sorbent Assay to Measure Nivolumab and Pembrolizumab Serum Concentrations - Basak, Edwin A; Wijkhuijs, Annemarie J M; Mathijssen, Ron H J; Koolen, Stijn L W; Schreurs, Marco W J (Therapeutic drug monitoring, 2018)
Treatment with monoclonal antibodies (mAbs) against programmed cell death protein 1 receptor is subject to high variation in treatment outcome among cancer patients. For these agents, no exposure-response (ER) relationships have been investigated in routine health care settings. However, ER relationships have been identified for several other mAbs used in oncology. Methods to conveniently measure serum concentrations of anti-programmed cell death protein 1 mAbs in routine health care may clarify possible ER relationships. Therefore, the authors aimed to develop an enzyme-linked immune sorbent assay (ELISA) for the measurement of both nivolumab and pembrolizumab serum concentrations of treated cancer patients. Optimal capture antigen and detection antibody concentrations were selected based on titrations. Nivolumab calibration standards ranging from 0.2 to 300 ng/mL were tested in duplicate. Accuracy was assessed in 2 recovery experiments. Intra- and interassay variations were assessed on 3 different days by 2 independent technicians. The developed ELISA was also set up for pembrolizumab calibration curves. Cross-reactivity of nivolumab measurements with ipilimumab was assessed. Of one nivolumab treated patient, serum concentrations in follow up samples were measured and presented. Nivolumab calibration standards of 0.20-25 ng/mL were used. Nivolumab trough concentrations after 1 cycle in 8 patients ranged from 17.3 to 31.1 mcg/mL. The range of accuracy was 84%-105%, whereas intra- and interassay variations showed a coefficient of variation of 5.5% and 10.1%, respectively. No cross-reactivity with ipilimumab was detected. Pembrolizumab trough concentrations (n = 8) ranged from 9.1 to 19.7 mcg/mL after 1 infusion. The in-house-developed ELISA provides the opportunity to measure both nivolumab and pembrolizumab serum concentrations. This may help identify possible ER relationships in treated cancer patients and may potentially lead to dose adjustments in the future.